Stylistic variation in three English translations of the Dead Sea Scrolls - J. A. Naudé (Acta Theologica)
Since the discovery of the Dead Sea Scrolls in 1947 different English translations were published. In this article the stylistic variation of three of these translations are analysed. It is suggested that the issue of stylistic variation boils down to linguistically inscribed preference in the choice and construction of discourses in the translated texts, i.e. a case of identifying the norms governing the patterning of translational behaviour within a given socio-cultural milieu. Vermes’ translation demonstrates the tendency to simplify the language used in translation. In the translation by Wise, Abegg & Cook there is an overall tendency to spell things out rather than leave them implicit. The translation of García Martínez demonstrates the trend towards general textual conventionality as opposed to textual creativity as in the case of the translation of Wise, Abegg & Cook and Vermes.